If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3e + 2f) + yf + 2 = 0 (3e * 3 + 2f * 3) + yf + 2 = 0 (9e + 6f) + yf + 2 = 0 Reorder the terms: 2 + 9e + 6f + fy = 0 Solving 2 + 9e + 6f + fy = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 9e + 6f + -2 + fy = 0 + -2 Reorder the terms: 2 + -2 + 9e + 6f + fy = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 9e + 6f + fy = 0 + -2 9e + 6f + fy = 0 + -2 Combine like terms: 0 + -2 = -2 9e + 6f + fy = -2 Add '-6f' to each side of the equation. 9e + 6f + -6f + fy = -2 + -6f Combine like terms: 6f + -6f = 0 9e + 0 + fy = -2 + -6f 9e + fy = -2 + -6f Add '-1fy' to each side of the equation. 9e + fy + -1fy = -2 + -6f + -1fy Combine like terms: fy + -1fy = 0 9e + 0 = -2 + -6f + -1fy 9e = -2 + -6f + -1fy Divide each side by '9'. e = -0.2222222222 + -0.6666666667f + -0.1111111111fy Simplifying e = -0.2222222222 + -0.6666666667f + -0.1111111111fy
| Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a | | 5/(b+5)-2/b | | 23x^2-15=6x | | 4/x=8/17 | | 9+4y=(3-y) | | -3(x+5)=2x+5 | | -4+5x=14-3x | | F(x)=2x-5 | | -18/-3 | | 34y+9=3(12y-18) | | 18x^3-9x^2-2x+1=0 | | 3+0.5x=4 | | x*0.3=460 | | F(3)=x+1 | | 21z=45-28z | | 2(x+3)=8x-18 | | 6y=(4y+18) | | 7-5(x+2)=3(x+2) | | F(x)=x+1 | | 12(4+6)-(8-7)=0 | | -3(3x+10)=4(x+2) | | 2/3x=24-10 | | 0=x+7x+12 | | (30-x)+3= | | -3(3x+10)=4(c+2) | | x*0.03=460 | | 7(7-3x)=x-11 |